Clinical efficacy of clonidine versus nalbuphine as intrathecal adjuvants to 0.5% hyperbaric bupivacaine for subarachnoid block during gynaecological procedures: a double blind study - Bansal, Manoranjan; Agarwal, Shikha; Gupta, Kumkum; Gupta, Prashant K.; Agarwal, Salony; Pandey, Mahesh N. (International Journal of Research in Medical Sciences, 2017)
Background: Regional anesthesia techniques for gynaecological procedures are on increasing trends due to their advantage of postoperative analgesia owing to intrathecal adjuvants. The present study was aimed to comparatively evaluate the clinical efficacy of clonidine with nalbuphine when co-administered intrathecally with 0.5% hyperbaric bupivacaine for gynaecological procedures. Methods: Regional anesthesia techniques for gynaecological procedures are on increasing trends due to their advantage of postoperative analgesia owing to intrathecal adjuvants. The present study was aimed to comparatively evaluate the clinical efficacy of clonidine with nalbuphine when co-administered intrathecally with 0.5% hyperbaric bupivacaine for gynaecological procedures. Results: The onset of sensory block was earlier in patients of Group BN (3.91±2.25 min vs 4.30±0.87 min, p=0.039). The onset of motor block was also earlier in patients of Group BN (p=0.042). The time to first rescue analgesia in patients receiving intrathecal clonidine was significantly delayed (283±14.18 min vs 231.50±26.18 min, p=0.001). Intraoperative hemodynamic changes were comparable and none of the patient suffered from respiratory depression, shivering, nausea or vomiting. Conclusions: Intrathecal clonidine as adjuvant to bupivacaine provided was clinically more effective than nalbuphine for prolonging the duration of analgesia for gynaecological procedures.